Preparation and characterization of chitosan/polyethylene glycol and cobalt ferrite magnetic-polymeric nanoparticles as resveratrol carriers: preparation, analytical methodology validation and in vitro applicability. Issue 2 (3rd April 2023) - Buratto, Ana Paula; Fontoura, Bruno Henrique; Carpes, Solange Teresinha; Almeida, Carlos Alberto Policiano
ABSTRACT: The objective of this research was to produce, characterize and evaluate biological activities of magnetic-polymeric nanoparticles loaded with resveratrol. Magnetic nanoparticles of cobalt ferrite (CoFe2 O4 ), polymeric nanoparticles of chitosan (CS) and polyethylene glycol (PEG), and polymeric-magnetic nanoparticles containing resveratrol (RSV) were developed. An analytical method using UV-VIS spectroscopy was developed and validated for the determination of RSV in the nanoparticles. The samples were analyzed by dynamic light scattering (DLS) for size, polydispersity index (PDI) and zeta potential. The encapsulation efficiency was determined by an indirect method. Antioxidants (ABTS and DPPH) and antibacterial (MIC and CBM) activities were evaluated. The average size of the nanoparticles varied between 184.6 and 276.5 nm. The magnetic-polymeric nanoparticles showed high encapsulation efficiency (EE) (98.75%) with a slow and prolonged release rate of 33.49% in 120 h. Furthermore, three months of storage showed less than 10% of RSV degradation. Its antioxidant activity (AA) was 170.55 mmol TE g −1 (by the ABTS method) and 130.60 mmol TE g −1 (by the DPPH method). The resveratrol-loaded magnetic-polymeric nanoparticles inhibited the growth of four tested bacteria. Their MIC values were less than 52.36 µg mL −1, and the CBM values of the nanoparticles >52.36 µg mL −1 . HIGHLIGHTS: Cobalt ferrite NPs coated with chitosan and polyethylene glycol were synthesized for the targeted delivery of resveratrol. CoFe2 O4 NPs coated with CS/PEG loaded with RSV showed average size of 234.40 nm. Resveratrol was encapsulated (>95%) onto CoFe2 O4 NPs coated with chitosan/PEG. RSV-loaded nanoparticles were effective as a scavenger of ABTS and DPPH radicals, suggesting applications in processes involving oxidative stress. RSV-loaded magnetic-polymeric NPs showed antibacterial activity against four Gram-negative and Gram-positive bacteria.